2020
DOI: 10.1016/j.schres.2020.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Indicated association between polygenic risk score and treatment-resistance in a naturalistic sample of patients with schizophrenia spectrum disorders

Abstract: Background: One third of people diagnosed with schizophrenia fail to respond adequately to antipsychotic medication, resulting in persisting disabling symptoms, higher rates of hospitalisation and higher costs for society. In an effort to better understand the mechanisms behind resistance to antipsychotic treatment in schizophrenia, we investigated its potential relationship to the genetic architecture of the disorder.Methods: Patients diagnosed with a schizophrenia spectrum disorder (N=321) were classified as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 77 publications
1
29
0
Order By: Relevance
“…higher symptom severity). 69 Several studies indicate that schizophrenia-PRS increases when comparing firstepisode psychosis to schizophrenia, and schizophrenia to TRS 20,[69][70][71] , although there is also conflicting evidence for the latter. 72,73 Bearing those former observations in mind, higher schizophrenia-PRS may characterize a subset of TRS-patients more likely to respond well to clozapine.…”
Section: Discussionmentioning
confidence: 99%
“…higher symptom severity). 69 Several studies indicate that schizophrenia-PRS increases when comparing firstepisode psychosis to schizophrenia, and schizophrenia to TRS 20,[69][70][71] , although there is also conflicting evidence for the latter. 72,73 Bearing those former observations in mind, higher schizophrenia-PRS may characterize a subset of TRS-patients more likely to respond well to clozapine.…”
Section: Discussionmentioning
confidence: 99%
“…Frank et al 45 reported a statistically significant association with history of clozapine treatment in patients with schizophrenia. However, different attempts to replicate this finding were generally negative, 46–49 although a positive result has been also reported 50 . Regarding psychopathology, SCZ PRS was associated with poorer response to antipsychotic treatment, measured as reduction in total symptom scores in first‐episode psychosis at 12‐weeks follow‐up in several cohorts 51 .…”
Section: Discussionmentioning
confidence: 96%
“…However, different attempts to replicate this finding were generally negative, [46][47][48][49] although a positive result has been also reported. 50 Regarding psychopathology, SCZ PRS was associated with poorer response to antipsychotic treatment, measured as reduction in total symptom scores in firstepisode psychosis at 12-weeks follow-up in several cohorts. 51 However, another study did not find association at about 9 weeks follow-up.…”
Section: Discussionmentioning
confidence: 97%
“…This is a major step in clarifying the application of GWAS results to SZ risk estimation ( Bigdeli et al, 2020 ). On the other hand, the evidence regarding the applicability of SZ polygenic risk scores to prediction of TRS is controversial, as results have been inconsistent ( Gasse et al, 2019 ; Werner et al, 2020 ; Wimberley et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%